Facing constitutive and normative aspects of different philosophical currents when approaching AI Ethics - Pinto, Fernando; Garcia, Ana Cristina (Anais da Conferência Latino-Americana de Ética em Inteligência Artificial (LAAI-Ethics); 2024: Anais da 1ª Conferência Latino-Americana de Ética em Inteligência Artificial, 2024)
Integrating artificial intelligence (AI), particularly machine learning, into legal decision-making is gaining prominence across various jurisdictions. While AI systems can offer efficiency and support in legal decisions, they also raise significant ethical concerns. This paper explores how AI systems, designed with underlying philosophical frameworks such as deontology and utilitarianism, can lead to conflicting outcomes when applied to legal judgments. The paper argues for a multidimensional ethical approach to AI in law that aligns with the legal philosophy of the respective jurisdiction while ensuring transparency, auditability, and fairness in decision-making processes.